KAJIAN SISTEM PENGELOLAAN LIMBAH BAHAN BERBAHAYA DAN BERACUN (B3) KEGIATAN PENDIDIKAN DI KAMPUS INSTITUT TEKNOLOGI SEPULUH NOPEMBER (ITS) - Susi Agustina Wilujeng (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2021)
Sepuluh Nopember Institute of Technology (ITS) has a total of 54 laboratories spread across four faculties and the Directorate of Research and Community Service of ITS (DRPM) laboratory. All laboratories are actively used for experiments and research. These activities certainly produce waste. Waste generated from activities in the laboratory is categorized as hazardous and toxic waste which in its management has special provisions. Currently, each laboratory already has a storage system for its waste, but not all of them meet the standards and requirements in accordance with the applicable laws and regulations. Several departments at ITS already have special WWTPs for laboratory waste but have not operated properly. In addition to waste from laboratory activities, ITS also produces specific types of hazardous waste. The waste is generated from office activities and student activities. Specific waste generation at ITS includes electronic waste and waste containing hazardous waste such as lamps, printer cartridges, batteries, and used packaging containing B3 waste. This research aims to support policy making which final result is the design of hazardous and toxic waste transfer station according to the needs and the amount of waste generated by each unit. The design is also equipped with certain facilities, such as standardizing safe packaging/containers for various characteristics of hazardous and toxic waste, laboratory waste safety storage racks, monitoring system, SOP (Standard Operating Procedure), providing labels and symbols according to waste characteristics, good ventilation, spill collection channels, as well as HSE support facilities (PPE box, first aid kit, emergency eye wash, emergency body wash, fire extinguisher).